PERENCANAAN OVERLAY JALAN BATAS SUMATERA SELATAN - SIMPANG EMPAT LAMPUNG: South Sumatra Border Road Overlay Planning - Simpang Empat Lampung - Mohammad Rizky Folanda; Sri Yuniarti (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2022)
Boundary road of South Sumatra - Simpang Empat is an access road from South Sumatra Province to Lampung Province or vice versa. Basically, the road has decreased its structural function as it increases with age. Research is needed to identify damage to the road. Aim to find out the consequences of road damage for road users, know the type of damage that occurred and know the design of additional layers of roads (Overlay). This research was conducted on the road section of South Sumatra - Simpang Empat, Lampung. By observing the condition of the damaged road and observing the type of damage and the percentage of damage. Average Daily Traffic Data obtained from the Transportation Office of Way Kanan Regency. Then the data that has been obtained is processed by component analysis methods. Based on the results of research on the type of road damage that occurred on the road section of South Sumatra - Simpang Empat, Lampung is the damage of the release of grains with a percentage of damage of 30%, damage to the hole with a percentage of 38%, damage to the discharge with a percentage of 21% and damage sungkur with a percentage of 11%. Overlays are done to reduce the impact caused by damage to the road. The arrangement of the bending pavement layer is the thickness of the surface layer (D1) 5 cm, the thickness of the foundation layer on the paved pavement (D2) 10 cm and the thick foundation layer of the top grained pavement (D3) 72 cm.